Experiences and needs of women in vulnerable situations receiving additional interventions in maternity care: a qualitative study - Esther I. Feijen-de Jong; Maria Dalmaijer; Relinde A. van der Stouwe; Danielle E. M. C. Jansen; J. Catja Warmelink (BMC, 2022)
Abstract Background Tailoring an intervention to the needs and wishes of pregnant women in vulnerable situations (e.g., socioeconomic disadvantages) can reduce the risk of adverse outcomes and empower these women. A relatively high percentage of pregnant women in the North of the Netherlands are considered vulnerable to adverse pregnancy outcomes because of their low socioeconomic status and the intergenerational transmission of poverty. In order to improve perinatal and maternal health, next to standard prenatal care, various interventions for pregnant women in vulnerable situations have been developed. We do not know to what extent these additional interventions suit the needs of (pregnant) women. Therefore, the aim of this study is to gain insight into the experiences and needs of women in vulnerable situations who receive additional maternity care interventions in the Northern Netherlands. Methods Qualitative research was performed. We used a phenomenological framework, which is geared towards understanding people's experiences in the context of their everyday lives. In-depth semi-structured interviews were conducted with 17 pregnant women in vulnerable situations living in the Northern Netherlands. A thematic analysis was carried out. Results We found three themes that reflect the experiences and needs of pregnant women in vulnerable situations in relation to the intervention they receive. These themes relate to the care provided by health professionals, to the impact of being offered an intervention, and to practical issues related to receiving an additional intervention. We found that the needs of pregnant women in vulnerable situations who received an additional maternity care intervention varied. This variation in needs was mainly related to practical issues. Women also expressed common needs, namely the desire to have control over their situation, the wish to receive tailor-made information about the intervention, and the wish for the intervention to be specifically tailored to their circumstances. Conclusions Living in vulnerable situations and being offered additional care evoked diverse reactions and emotions from pregnant women. We recommend that health professionals ensure open and clear communication with women, that they ensure continuity of care and relationship-centered care, and that they become aware of the process of stigmatization of women in vulnerable situations.